Influence of Age at Harvest and Packaging Conditions on Color Stability of Bovine Psoas major Muscle - Xiao Lu; Xin Luo; Sulaiman K. Matarneh (Foods)
This study investigated the effect of cattle age on the color stability of Psoas major steaks under different packaging conditions, including polyvinyl chloride (PVC) film packaging, high-oxygen-modified atmosphere packaging (HiOx-MAP), and carbon monoxide-modified atmosphere packaging (CO-MAP), over a 14-day storage period. Steaks from old cows had a greater myoglobin content than those from young animals (p < 0.05), resulting in a darker beef color. Regardless of animal age, steaks in PVC and HiOx-MAP exhibited poor color stability during storage, as evidenced by the low color intensity and high surface metmyoglobin (MetMb; p < 0.05). These samples also exhibited a reduced MetMb reducing activity (MRA) and oxygen consumption rate (OCR) and higher 2-thiobarbituric acid reactive substance (TBARS) levels, with these effects being evident in steaks from mature cows. In contrast, steaks stored in CO-MAP had greater redness, MRA, and OCR, along with lower surface MetMb and TBARS levels (p < 0.05), contributing to the limited discoloration of steaks from both age groups. These findings suggest that while both harvest age and packaging affect the shelf stability of bovine steaks, packaging plays a more significant role. CO-MAP proved to be more effective than aerobic packaging and may mitigate age-related differences in color stability.